Babel - Jones, Ifan Morgan (Y Lolfa, 2019)
Fast-paced mystery set in an industrial town in the second half of the 19th century. The main character, Sara, escapes from her fath er, an alcoholic minister and comes to the town having seen an adv ert for a job as a journalist in Henry Glass's press, a business m an and a editor of newspaper, Llais y Bobol. Intro – Babel_-_Ifan_Morgan_Jones – Babel_-_Ifan_Morgan_Jones-1 – Babel_-_Ifan_Morgan_Jones-2 – Babel_-_Ifan_Morgan_Jones-3 – Babel_-_Ifan_Morgan_Jones-4 – Babel_-_Ifan_Morgan_Jones-5.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books